ENVIRONMENTAL LAW IN APARTMENT DEVELOPMENT IN LARGE CITIES - Augustinus Setijanto (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
This study aims to analyze the legal responsibilities of developers and contractors in apartment construction under Indonesian environmental law and to examine the roles of Environmental, Social, and Governance (ESG), Environmental Governance, and Relational Governance in the prevention of environmental disputes. This study employs a normative legal methodology using legislative, conceptual, and case study approaches to examine the construction of the Uttara Yogyakarta Apartment and the LA City Jakarta Apartment. The results indicate that environmental disputes are not only caused by physical environmental damage but also by failures in the governance of relationships among stakeholders. Compliance with Law No. 32 of 2009 is a minimum requirement, whereas the success of sustainable development requires community participation, transparency, communication, trust, and good governance. This study proposes a conceptual model, the Relationship-Based Environmental Governance Theory, which links ESG Compliance, Environmental Governance, Stakeholder Trust, Social License to Operate, and Dispute Avoidance as a new paradigm in construction environmental law.